2014
DOI: 10.18632/oncotarget.3104
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of EP2/EP4 signaling abrogates IGF-1R-mediated cancer cell growth: Involvement of protein kinase C-θ activation

Abstract: Associations between growth factor receptor-mediated cell signaling and cancer cell growth have been previously characterized. Receptors for prostaglandin E2, such as EP2, and EP4, play roles in cancer growth, progression and invasion. Thus, we examined the interactions between EP2/EP4- and IGF-1R-mediated cellular signaling in human pancreatic cancer cells. Selective antagonists against EP2 and EP4 abrogated IGF-1-stimulated cell growth and suppressed MEK/ERK phosphorylation. In subsequent experiments, phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…Our results indicated the critical role of EP4 involved in the effect of solamargine on inhibition of lung cancer cell growth, implying that EP4 could be a potential target in the treatment of lung cancer. Recent studies showed that inhibition of EP4 suppressed growth of several cancer cell types emphasizing the important role of this prostanoid receptor [ 34 , 35 ]. We believed that, as unfavorable tumor-promoting role, EP4 could be a new target in mediating the inhibitory effect of solamargine in lung cancer intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated the critical role of EP4 involved in the effect of solamargine on inhibition of lung cancer cell growth, implying that EP4 could be a potential target in the treatment of lung cancer. Recent studies showed that inhibition of EP4 suppressed growth of several cancer cell types emphasizing the important role of this prostanoid receptor [ 34 , 35 ]. We believed that, as unfavorable tumor-promoting role, EP4 could be a new target in mediating the inhibitory effect of solamargine in lung cancer intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer, EP4 occupation leads to ERK activation supporting anchorage-independent growth and resistance to apoptosis that is reversed by small molecule EP4 antagonists ONO-AE3-208 and AH23848 (Hawcroft et al, 2007). Likewise, inhibition of the EP2 and EP4 receptors (with AH6809 and GW627368X, respectively) represses IGF-1-induced proliferation of pancreatic BxPC-3 cancer cells (Takahashi et al, 2019) and is accompanied by increased phospho-PKC-q and decreased phospho-ERK (Takahashi et al, 2015).…”
Section: The Role Of Ep4 In Cell Proliferationmentioning
confidence: 99%
“…40 EP2 has been demonstrated to promote the activation of ERK signal and promote the formation of pancreatic cancer in mice. 41 More interestingly, our results of Western blot showed that the Akt pathway was significantly activated, not ERK pathway after interfering with the expression of GRK2 in HCC cells by siRNA. The above results suggest that GRK2 may inhibit the invasion and metastasis of HCC by inhibiting the EP2 receptor-mediated Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 72%